Autochthonous Cases of Dirofilaria in Dogs from TimiE County (Western Part) Romania (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: dirofilaria immitis; dirofilaria repens; dog; timi#x15F; county; romania